Studi Etnofarmasi Suku Osing Kecamatan Kabat, Singojuruh dan Rogojampi - Auralia Putri Pratama; Debi Listiayana; Dedi Irawanto; Jacinda Na’ilahafitra; Rismatul Khoiroh; Yuniatin Hasanah; Indah Yulia Ningsih; Evi Umayah Ulfa (The Ethnobiological Society of Indonesia, 2021)
Medicinal plants have been widely used for public health maintenance. Ethnic traditional medicine traditions can be used as a reference for the discovery of new medicines from natural ingredients. The Osing tribe that inhabits several areas in Banyuwangi Regency, including in Kabat District, Singojuruh District and Rogojampi District, has traditional medicine passed down by their ancestors and has not been well documented. The purpose of this ethnopharmaceutical study is to document the knowledge of traditional medicine of the Osing tribe and identify plant species used for medicine. Traditional medicine knowledge was carried out by semi-structural interviews using open-ended questions with 24 informants. Data were analyzed with the value of Used Value (UV) and Informant Consensus Factor (ICF). The results of the study recorded 30 types of plants, nine types of animals and four types of minerals used by the Osing tribe for treatment. Plants that have UV values above 0.5 are Curcuma longa (1,208), Stenosemia aurita (Sw) C. presl (0.625), and Moringa oleifera (0.625). The parts of the plant that were widely used were leaves (36.39%), rhizomes (20.65%) and fruit (18.68%). The highest ICF value in this study was conjunctivitis (0.8) with the medicinal plant used, namely Stenosemia aurita Sw C. Presl. This study shows that medicinal plants play a very important role in maintaining the health of the Osing people.